P134: Organizational interventions and policies to support second victims in acute care settings: a scoping study. (May 2019) - Wade, L.; Williams, N.; Fitzpatrick, E.; Parker, R.; Hurley, K.
Abstract : Introduction : The harm that may come to healthcare providers impacted by adverse events has led them to be called "second victims." Our objective was to characterize the range and context of interventions used to support second victims in acute care settings.Methods : We performed a scoping study using the process described by Arksey and O'Malley. Comprehensive searches of scientific databases and grey literature were conducted in September 2017 and updated in November 2018. A library scientist searched PubMed, CINAHL, EMBASE and CENTRAL. We sought unpublished literature (Canadian Electronic Library, Proquest and Scopus) and searched reference lists of included studies. Stakeholder organizations and authors of included studies were contacted through email, requesting information on relevant programs. Two reviewers independently reviewed titles and abstracts using predetermined criteria. Using a structured data abstraction form, two reviewers independently extracted data and appraised methodological quality with the Mixed Methods Appraisal Tool (MMAT). All discrepancies were resolved through consensus. A qualitative approach was used to categorize the context and characteristics of the identified strategies and interventions.Results : Our search strategy yielded 3883 results. After screening titles and abstracts, 173 studies underwent full text screening. Extracted data reflected 21 interventions categorized as providing peer-support (n = 7), proactive education (n = 7) or both (n = 7). Programs came from Canada (n = 2), Spain (n = 2), and United States (n = 17). Specific traumatic events were described as the trigger for development of five programs. While some programs were confined to a standard definition of second victim as a healthcare provider traumatized by an "unanticipated adverse patient event" (n = 6), other programs had a broader scope (n = 12) including situations such as non-accidental trauma, stressful anticipated patient events and complaints/litigation (3 programs were unclear about the definition). Confidentiality was assured in nine peer support programs. Outcome measures were often not reported and were limited in terms of quality.Conclusion : This is a new area of study with little scientific rigour from which to determine whether these programs are effective. Concerns about protecting healthcare providers from potential legal proceedings hinder documentation and study of program effectiveness.